Mobility and the lifetime distributional impact of tax and transfer reforms - Peter Levell; Barra Roantree; Jonathan Shaw (Institute for Fiscal Studies (IFS), 2016)
The distributional impact of proposed reforms plays a central role in public debates around tax and transfer policy. We show that accounting for realistic patterns of mobility in employment, earnings and household circumstances over the life-cycle greatly affects our assessment of the distributional effects of tax and transfer reforms. We focus on three reforms modelled in the UK context: (i) changes to out-of-work versus in-work benefits, (ii) adjustments to income tax rates, and (iii) reforms to indirect taxation. In all three cases, the long-run distributional impact differs to that implied by a standard crosssection analysis in important ways.
Keywords: D31; H20; H24; 330; inequality; redistribution; income mobility; lifetime; tax and transfer reform